Feetness Tracker / Muhammad Nor Azam Zainol Abidin - Zainol Abidin, Muhammad Nor Azam; Pauzi, Faizul Amir; Ramli, Seri Nur Amirah; Abd Aziz, Nurul Natalia (2022)
This study was focusing on the development of smart running shoes which is named Feetness Tracker. This study also conducted to gain a deeper understanding and get additional information about the product. This study will focus on the improvements that will be implemented to the regular running shoes. The flaws of the regular running shoes by top sports brands are being discussed in order to generate the best solution for smart running shoes. Lastly, the new product development was studied to further strengthen the findings of this development of Feetness Tracker.